2012
DOI: 10.4077/cjp.2012.amm121
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Protein Kinase Cα and the MZF-1 and Elk-1 Transcription Factors in Human Bladder Transitional Cell Carcinoma Cells

Abstract: In a recent study on hepatocellular carcinoma (HCC), we have shown that the transcription factors Myeloid Zinc Finger-1 (MZF-1) and Ets-like-protein 1 (Elk-1) are significantly related to protein kinase C alpha (PKCα) expression. The purpose of this study was to determine the correlation of the expression of PKCα with the expression of Elk-1 and MZF-1 in various differentiated urinary bladder transitional cell carcinoma (TCC) cell lines: 5637, BFTC905, TSGH8301, HT1376 and HT1197 cells. The malignant potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, none of these studies have assessed the prognostic value of ELK1 or p-ELK1 expression. On the other hand, the expression levels of ELK1 [ 37 ] and p-ELK1 [ 38 ] have been determined in bladder cancer cell lines. Our immunohistochemical staining in bladder tissue microarrays (TMAs) showed that, compared with non-neoplastic urothelium, significant increases in the expression of ELK1 and p-ELK1 were observed in bladder tumor.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies have assessed the prognostic value of ELK1 or p-ELK1 expression. On the other hand, the expression levels of ELK1 [ 37 ] and p-ELK1 [ 38 ] have been determined in bladder cancer cell lines. Our immunohistochemical staining in bladder tissue microarrays (TMAs) showed that, compared with non-neoplastic urothelium, significant increases in the expression of ELK1 and p-ELK1 were observed in bladder tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro assays have indicated that overexpression of SRF in thyroid cancer cells enhances the expression level of c-Fos protein, cell migration, and invasiveness 20 . The role of MZF1 in thyroid cancer has never been investigated, however, it was involved in colorectal, cervical, and bladder carcinogenesis 21 22 23 .…”
Section: Discussionmentioning
confidence: 99%